Răspuns:
1. a) 18 [tex]a^{2}b^{2}[/tex] ( b+ 3ab - 2a)
b) [tex]y^{2} t^{2}[/tex] [tex]\sqrt{5}[/tex]*( 3y- 2*5[tex]y^{2}[/tex]t + 16t)=[tex]y^{2} t^{2}[/tex][tex]\sqrt{5}[/tex] *( 3y- 10[tex]y^{2}[/tex]t +16t)
2. a) 9[tex]x^{2}[/tex] - 24x+ 16
b) 81[tex]x^{2}[/tex] -9x[tex]\sqrt{2}[/tex] + 9x[tex]\sqrt{2}[/tex] - 2= 81 [tex]x^{2}[/tex] -2
c) (5- 4y) [tex](5-4y)^{2}[/tex]= (5-4y)*( 25-40y +16[tex]y^{2}[/tex])= 125 - 200y +80[tex]y^{2}[/tex] - 100y + 160[tex]y^{2}[/tex] - -64[tex]y^{3}[/tex] = 125 -64[tex]y^{3}[/tex] +240[tex]y^{2}[/tex] -300 y
3. a) [tex](x- \sqrt{2} )^{2}[/tex]
b) [tex](x+2)^{3}[/tex]